2009
DOI: 10.1002/chem.200802086
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Insights into the Trinuclear Ferrocenophane and Unexpected Hydrido Inverse Crown Products of Alkali‐Metal‐Mediated Manganation(II) of Ferrocene

Abstract: With the aim of introducing the diisopropylamide [NiPr2]− ligand to alkali‐metal‐mediated manganation (AMMMn) chemistry, the temperature‐dependent reactions of a 1:1:3 mixture of butylsodium, bis(trimethylsilylmethyl)manganese(II), and diisopropylamine with ferrocene in hexane/toluene have been investigated. Performed at reflux temperature, the reaction affords the surprising, ferrocene‐free, hydrido product [Na2Mn2 (μ‐H)2{N(iPr)2}4]⋅2 toluene (1), the first Mn hydrido inverse crown complex. Repeating the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…147,148 The more challenging metallation of non-substituted naphthalene has also been accomplished by the Lochmann-Schlosser superbase ( n BuLi$KO t Bu, LICKOR) which can di-deprotonate naphthalene at cryogenic temperatures, but not in a regioselective manner as twelve different mono/di-substituted isomers are formed in a collectively poor yield. 121 Synergically-operative metallators such as sodium zincate (TMEDA)$Na(m-TMP)(m-t Bu) Zn( t Bu) [149][150][151][152][153][154][155] or sodium manganate (TMEDA)$Na(m-TMP)(m-CH 2 SiMe 3 )Mn(TMP) 119,[156][157][158][159] offer an enhanced regioselectivity. Metallation (zincation 120 or manganation 119 ) at the 2-position of naphthalene occurs at room temperature via these respective reagents.…”
Section: Application Of Potassium Pre-inverse-crowns In the Synthesis...mentioning
confidence: 99%
“…147,148 The more challenging metallation of non-substituted naphthalene has also been accomplished by the Lochmann-Schlosser superbase ( n BuLi$KO t Bu, LICKOR) which can di-deprotonate naphthalene at cryogenic temperatures, but not in a regioselective manner as twelve different mono/di-substituted isomers are formed in a collectively poor yield. 121 Synergically-operative metallators such as sodium zincate (TMEDA)$Na(m-TMP)(m-t Bu) Zn( t Bu) [149][150][151][152][153][154][155] or sodium manganate (TMEDA)$Na(m-TMP)(m-CH 2 SiMe 3 )Mn(TMP) 119,[156][157][158][159] offer an enhanced regioselectivity. Metallation (zincation 120 or manganation 119 ) at the 2-position of naphthalene occurs at room temperature via these respective reagents.…”
Section: Application Of Potassium Pre-inverse-crowns In the Synthesis...mentioning
confidence: 99%
“…To date, several examples of [1]­ferrocenophanes have been reported that feature bonds to either main group elements or transition metal ions. Structurally characterized examples include compounds with bridging atoms from group 13 (B, Al), , group 14 (Si, Ge, Sn), ,, group 15 (P, As), , group 16 (S, Se), , as well as diamagnetic (Zr, Ni, Pd, Pt) and paramagnetic (Fe, Mn) transition metal complexes (see Figure for selected examples). Importantly, [1]­ferrocenophanes possessing f-block elements in the bridgehead have remained largely unexplored.…”
mentioning
confidence: 99%
“…66 These complexes typically consist of a bimetallic magnesium/alkali metal core, 36,56,66,67 with the notable exception of the manganese/ sodium complex [Na 2 Mn 2 (μ-H) 2 {N(iPr) 2 } 4 ]•2 toluene discovered serendipitously in 2009 during attempts to metalate ferrocene with manganese. 68 The iron hydride complex 5 (Figure 1) crystallizes in the space group P2/n and has identical unit cell parameters to those of the tetrameric transition metal(I) silylamide complexes {MN(SiMe 3 ) 2 } 4 (M = Co, Ni, Cu, Ag). 35,69−71 Like these complexes, 5 is comprised of four metal atoms in a planar arrangement bridged by four silylamide ligands having coplanar nitrogen atoms.…”
Section: ■ Experimental Detailsmentioning
confidence: 99%